Environment-friendly nanocellulose-indigo dyeing of textiles. Issue 20 (11th August 2021) - Rai, Smriti; Saremi, Raha; Sharma, Suraj; Minko, Sergiy
Abstract : Nanofibrillated cellulose technology in combination with chitosan additives provides a sustainable and environmentally sound technology for indigo dyeing of cotton fabrics. Abstract : Dyeing of one pair of blue denim jeans consumes about 50–100 liters of water loaded with toxic reducing agents and alkali that remain as effluents in wastewater. Here we introduce an environmentally sound indigo-dyeing technology utilizing a high surface to volume ratio of nanocellulosic materials, which reduces water consumption up to a factor of 25 and eliminates the use of any reducing agent or alkali. This technology secures over 90% dye fixation compared to the 70–80% of conventional dyeing. Lighter or darker shades are approached in a one-step process compared to traditional vat dyeing with multiple (up to 8) dips in a reducing vat followed by oxidation. The dyeing process is as simple as the deposition of a nanocellulose hydrogel loaded with fine natural indigo particles and chitosan over the cotton denim fabric or yarn. The generated nanofibrillated cellulose mesh-like conformal coating encloses indigo particles, whereas chitosan improves the fixation and adhesion of the coating to fabrics via physical cross-linking.